Surveying on the Preparation of Foreign Master Students in Faculty of Music Bangkothonburi University - Jantaramanee , Jantimaporn; Gatemuan, Kampanat (Journal of Roi Kaensarn Academi, 2024)
The purpose of this research was to study the level of readiness before entering further studies of international graduate students, Faculty of Music, Bangkokthonburi University, academic year 2024. This research used quantitative method used a survey-based study utilizing a mixed-methods approach. sample survey included 142 respondents with 76 master's and 66 doctoral degree, The research tools included questionnaire, and data analysis of questionnaires from online surveys It's an average and a percentage. The results of the research found that Thai culture's readiness for Chinese graduate students is influenced by language proficiency, cultural communication, and cross-cultural adaptation. Chinese students often face language barriers and translanguaging issues. Academic and work readiness factors include cognitive abilities, soft skills, political stability, security, and education quality. Strategies to improve research visibility, open access, and presenting research at conferences are essential. Universities should develop mechanisms to prepare students and address job market competition and visa regulations. indicating a moderate to very ready level of English readiness. Thai language readiness was low, but knowledge of Thai culture was ready. The respondents had a high level of academic readiness, with an average readiness of 4.09 or 81.83 percent. They had moderate readiness for research issues and academic article writing. Concerns and expectations were high, with an average readiness of 3.94 or 78.71 percent.